2008
DOI: 10.1161/circresaha.107.165183
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of the Central Nervous System β-Adrenoceptor Blockade on the Failing Heart

Abstract: Heart failure patients are routinely given ␤-adrenoceptor antagonists (␤-blockers), although the mechanism(s) underlying their beneficial effects is not fully resolved. It is not entirely clear how long-term application of negative inotropic compounds improves cardiac performance, slows remodeling processes, and decreases mortality. All ␤-blockers, which produce a beneficial effect in heart failure, have in common a high degree of lipophilicity and, therefore, have the ability to cross the blood-brain barrier.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 32 publications
0
21
0
2
Order By: Relevance
“…71 However, the actions of metoprolol within the central nervous system appear to exert favourable effects on the failing rat heart, likely due to reductions in cardiac sympathetic outflow. 72 Whether these previously unrecognised pleiotropic effects of b-adrenergic blockade are manifested in human hypertension remains to be determined. Of note, despite lowering blood pressure certain diuretics (for example, chlorthalidone 73 ), dihydropridine calcium channel blockers 74 and combination therapies (for example, AT1-R antagonism plus diuretic 75 ) may actually raise SNA due to baroreceptor unloading.…”
Section: 65mentioning
confidence: 99%
See 1 more Smart Citation
“…71 However, the actions of metoprolol within the central nervous system appear to exert favourable effects on the failing rat heart, likely due to reductions in cardiac sympathetic outflow. 72 Whether these previously unrecognised pleiotropic effects of b-adrenergic blockade are manifested in human hypertension remains to be determined. Of note, despite lowering blood pressure certain diuretics (for example, chlorthalidone 73 ), dihydropridine calcium channel blockers 74 and combination therapies (for example, AT1-R antagonism plus diuretic 75 ) may actually raise SNA due to baroreceptor unloading.…”
Section: 65mentioning
confidence: 99%
“…98 Following animal studies first conducted over 50 years ago 99,100 and extensive technical development work, 101,102 surgical implantation of a device eliciting chronic carotid baroreflex stimulation (Rheo, CVRx, Minneapolis, MN, USA) has recently been demonstrated to effectively lower blood pressure and muscle SNA in humans. 14,71,72,103,104 This has been based on the recently resurrected idea that arterial baroreceptors control arterial pressure in the long term. 105 In his original study, Thrasher (2002) showed that unloading of baroreceptors at one carotid sinus (with all other arterial baroreceptors denervated) caused a sustained pressor response lasting up to 3 weeks in conscious dogs.…”
Section: Drug-resistant Hypertension-how To Treat?mentioning
confidence: 99%
“…Furthermore, it has been demonstrated that intracerebroventricular administration of metoprolol, which induces blockade of central b-adrenergic receptors without peripheral effects, attenuates the progression of left ventricular remodeling in a rat model of heart failure. These data clearly show there is a role of the central action of certain b-blockers in their beneficial effect on the failing heart [18,19].…”
Section: The Brain As a Target For Development Of New Class Of Drugs mentioning
confidence: 77%
“…Rat models have been widely used in the study of the pathophysiology of cardiovascular diseases and testing effects of medical therapies (1,9,19). One of important findings of this study is to demonstrate for the first time that a rat model of chronic organic MR expresses a pathophysiology similar to humans.…”
Section: Discussionmentioning
confidence: 96%